Predator–prey mass ratio drives microbial activity under dry conditions in Sphagnum peatlands. Issue 11 (12th May 2018) - Reczuga, Monika K.; Lamentowicz, Mariusz; Mulot, Matthieu; Mitchell, Edward A. D.; Buttler, Alexandre; Chojnicki, Bogdan; Słowiński, Michał; Binet, Philippe; Chiapusio, Geneviève; Gilbert, Daniel; Słowińska, Sandra; Jassey, Vincent E. J.
Abstract: Mid‐ to high‐latitude peatlands are a major terrestrial carbon stock but become carbon sources during droughts, which are increasingly frequent as a result of climate warming. A critical question within this context is the sensitivity to drought of peatland microbial food webs. Microbiota drive key ecological and biogeochemical processes, but their response to drought is likely to impact these processes. Peatland food webs have, however, been little studied, especially the response of microbial predators. We studied the response of microbial predators (testate amoebae, ciliates, rotifers, and nematodes) living in Sphagnum moss carpet to droughts, and their influence on lower trophic levels and on related microbial enzyme activity. We assessed the impact of reduced water availability on microbial predators in two peatlands using experimental (Linje mire, Poland) and natural (Forbonnet mire, France) water level gradients, reflecting a sudden change in moisture regime (Linje), and a typically drier environment (Forbonnet). The sensitivity of different microbial groups to drought was size dependent; large sized microbiota such as testate amoebae declined most under dry conditions (−41% in Forbonnet and −80% in Linje). These shifts caused a decrease in the predator–prey mass ratio (PPMR). We related microbial enzymatic activity to PPMR; we found that a decrease in PPMR can have divergent effects on microbial enzymatic activity. In a community adapted to drier conditions, decreasing PPMR stimulated microbial enzyme activity, while in extreme drought experiment, it reduced microbial activity. These results suggest that microbial enzymatic activity resulting from food web structure is optimal only within a certain range of PPMR, and that different trophic mechanisms are involved in the response of peatlands to droughts. Our findings confirm the importance of large microbial consumers living at the surface of peatlands on the functioning of peatlands, and illustrate their value as early warning indicators of change. Abstract : We studied the response of microbial predators living in Sphagnum moss carpet to droughts and related it to ecosystem functioning. Our results suggest that microbial enzymatic activity resulting from food web structure is optimal only within a certain range of predator–prey mass ratio (PPMR), and that different trophic mechanisms are involved in the response of peatland to droughts. Our findings confirm the importance of large microbial consumers living at the surface of peatlands in the functioning of peatlands, and raise their value as early warning bioindicators.